Pengaruh Character dan Capacity Debitur terhadap Keputusan Persetujuan Kredit pada PT Bank Perkreditan Rakyat (BPR) Mambal, Bali - PRATAMA, IDA BAGUS AGUNG ADHITYA; DEWI, NI LUH PRIMA KEMALA; YUDHARI, I DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.2, Desember 2024, 2024)
The Influence of  Character  and Borrower  Capacity  on Credit Approval Decisions at PT People's Credit Banks (BPR) Mambal, Bali.  The main objective of national development is to create a just and prosperous society, with the banking sector playing a crucial role in supporting economic development through the provision of credit to individuals and companies. However, the province of Bali has experienced significant negative impacts due to the Covid-19 pandemic, particularly in the health and economic sectors. People's Credit Banks (BPR) in Bali have witnessed a decline in performance during the pandemic, especially in relation to  non-performing loans . Therefore, BPR needs to exercise caution in granting credit by considering the  character  and  capacity  of borrowers. This study aims to examine the influence of  character  and  capacity  on credit approval decisions at PT Bank Perkreditan Rakyat (BPR) Mambal. The research population consists of 30 customers of PT Bank Perkreditan Rakyat (BPR) Mambal, selected through  accidental sampling . The research instruments used include interviews, documentation, and literature review. The data were analyzed using descriptive analysis with the  Structural Equation Model-Partial Least Square  (SEM-PLS) method. The research findings indicate that the  character  and  capacity  of customers have a positive and significant influence on credit approval decisions. The implications of this study emphasize the importance for PT Bank Perkreditan Rakyat (BPR) Mambal to seriously consider the  character  and  capacity  of customers when making credit approval decisions. This approach will enhance the success and feasibility of the credit provided, reduce the risk of  non-performing loans , and increase customer trust. The researchers also recommend that BPR conduct regular evaluations of customers and improve communication with them to ensure the preservation of their  character  and  capacity . Additionally, leveraging appropriate information technology can optimize the customer evaluation and monitoring processes.